KEKUATAN TEKAN DAN POLA FRAKTUR ONLAY RESIN KOMPOSIT SEMI DIREK DENGAN TEPI KAVITAS BERBENTUK BEVEL DAN BUTT-JOINT PADA GIGI PASCA PERAWATAN ENDODONTI: COMPRESSIVE STRENGTH AND FRACTURE PATTERN OF SEMI-DIRECT RESIN COMPOSITE ONLAY RESTORATION WITH BEVEL AND BUTT-JOINT CAVO SURFACE MARGINS IN ROOT CANA - Epita Sarah Pane,; Debora Natalyna, (Dentika: Dental Journal, 2010)
Onlay is one of the recommended final restoration for root canal treated teeth and resin composite is a material of choice for making onlay and can be done in semi-direct method. Bevel and butt-joint cavo surface margins have been suggested in inlay restoration and this study was conducted to evaluate the compressive strengths and fracture patterns of both type of margins in semi-direct onlays. Sixteen upper premolars were mounted in 45 degree angle and loaded with compressive tests with Universal Testing Machine. Mean compressive strength of group with bevel margin was 900,62 ï‚± 171,27 N, and 1021,40 ï‚± 183,87 N for the butt-joint group. This difference was not significant statistically (p=0,208). Onlays with bevel margin, fractured at the onlay, the junction between onlay and tooth and at the tooth, and were mainly affected the buccal cusp. For the butt-joint group, fractured mainly occurred at the onlays and affected the buccal and palatal cusps. In conclusion, the choice of cavosurface margin resin composite onlay restoration in root canal treated teeth is according to clinician’s desire and skill.